Three-dimensional analysis of reinforced concrete members via embedded discontinuity finite elements - Manzoli, O. L. [UNESP]; Oliver, J.; Diaz, G.; Huespe, A. E. (IBRACON - Instituto Brasileiro do Concreto, 2008)
This paper presents a methodology to model three-dimensional reinforced concrete members by means of embedded discontinuity elements based on the Continuous Strong Discontinuous Approach (CSDA). Mixture theory concepts are used to model reinforced concrete as a 3D composite material constituted of concrete with long fiber bundles (rebars) oriented in different directions embedded in it. The effects of the rebars are provided by phenomenological constitutive models designed to reproduce the axial non-linear behavior, as well as bond-slip and dowel action. This paper is focused on the constitutive models assumed for the components and the compatibility conditions chosen to constitute the composite. Numerical analyses of existing experimental reinforced concrete members are presented, illustrating the applicability of the methodology.

Apresenta-se uma metodologia para modelar elementos estruturais de concreto armado tridimensionais através de elementos finitos com descontinuidade incorporada no contexto da aproximação contínua de descontinuidades fortes. Utilizam-se conceitos de teoria de misturas para representar o concreto armado como um material composto de matriz (concreto) com feixes de fibras (barras de aço) longas em diferentes direções. O efeito das barras é proporcionado por modelos constitutivos fenomenológicos, desenvolvidos para reproduzir o comportamento axial não-linear, assim como efeitos provenientes de deslizamento por perda de aderência e ação de pino. O presente artigo foca os modelos constitutivos dos componentes e as condições de compatibilidade escolhidas para constituir o composto. Para ilustrar a aplicabilidade da metodologia proposta, apresentam-se análises numéricas de testes experimentais de elementos de concreto armado existentes.
Análise tridimensional de elementos estruturais de concreto armado via elementos finitos com descontinuidades incorporadas
Keywords: elementos finitos; mecânica de fratura; descontinuidades fortes; teoria de misturas; fissuras incorporadas; finite elements; fracture mechanics; strong discontinuities; mixture theory; embedded cracks